EVOLUŢIA CONCEPTULUI DE WEB ŞI GRADUL DE INTERACTIVITATE AL INTERACŢIUNILOR ÎN ÎNVĂŢĂMÂNTUL ELECTRONIC - USM ADMIN (Moldova State University, 2010)
The article presents the analysis of the Web concept evolution from the didactic point of view. The Web represents one of the most known Internet services. The Internet and the Web are watched as a new stage of the technological micro-revolutions in learning. There are investigated in the article the didactic characteristics of the Web: publication, communication and the access from the perspective of interaction interactivity in e-learning.